2020
DOI: 10.1371/journal.pone.0228379
|View full text |Cite
|
Sign up to set email alerts
|

Measuring next of kin’s experience of participation in the care of older people in nursing homes

Abstract: Background Lack of conceptual clarity and measurement methods have led to underdeveloped efforts to measure experience of participation in care by next of kin to older people in nursing homes. Objective We sought to assess the measurement properties of items aimed at operationalizing participation in care by next of kin, applied in nursing homes. Methods A total of 37 items operationalizing participation were administered via a questionnaire to 364 next of kin of older people in nursing homes. Measurement prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 59 publications
1
13
0
1
Order By: Relevance
“…Em estudo internacional que avaliou a experiência de familiares no cuidado a idosos institucionalizados, evidenciou-se que a participação da família estava relacionada à proximidade com a equipe, assim como a relação de confiança entre os mesmos, o diálogo aberto sobre o idoso, ser convidado para concluir tarefas, respeitado pelo próprio conhecimento e reconhecido pela equipe como parte do cuidado (23) . Nesta perspectiva, a comunicação da equipe com os familiares de idosos pode ser instrumento facilitador na cooperação e participação familiar, assim como barreira, quando utilizada somente para comunicar incidentes ou alterações clínicas, não valorizando a família como importante colaborador das práticas de cuidado ou tomada de decisão (24) .…”
Section: Resultsunclassified
“…Em estudo internacional que avaliou a experiência de familiares no cuidado a idosos institucionalizados, evidenciou-se que a participação da família estava relacionada à proximidade com a equipe, assim como a relação de confiança entre os mesmos, o diálogo aberto sobre o idoso, ser convidado para concluir tarefas, respeitado pelo próprio conhecimento e reconhecido pela equipe como parte do cuidado (23) . Nesta perspectiva, a comunicação da equipe com os familiares de idosos pode ser instrumento facilitador na cooperação e participação familiar, assim como barreira, quando utilizada somente para comunicar incidentes ou alterações clínicas, não valorizando a família como importante colaborador das práticas de cuidado ou tomada de decisão (24) .…”
Section: Resultsunclassified
“…First, when focusing on the individual level of change, the intervention can be regarded as successful for CaT but not as successful for CiC. This finding was somewhat expected because it has been hypothesised that it is easier for care interventions to achieve success in improving CaT than in improving CiC [ 11 ]. Previous research has shown somewhat similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The NoK-PiC scale consists of two subscales, the CaT and the CiC, which can either be used separately or combined to produce a total score. The scales meet rigorous measurement standards, having, for instance, no differential item functioning, high person separation indexes and no disordered thresholds [ 11 ]. The subscales contain nine items each, and all items are scored from 0 to 4 ( do not agree at all [= 0]; agree to a low extent [= 1]; partially agree [= 2]; agree to a high extent [= 3] and totally agree [= 4]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations